2021
DOI: 10.1210/endocr/bqab011
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Divergent Observations Regarding Osteocalcin/GPRC6A Endocrine Signaling

Abstract: A new schema proposes that the bone-derived osteocalcin (Ocn) peptide hormone activates the G- protein coupled receptor GPRC6A to directly regulate glucose and fat metabolism in liver, muscle and fat, and to stimulate the release of metabolism-regulating hormones, including insulin, fibroblast growth factor 21, glucagon-like peptide 1, testosterone and interleukin 6. Ocn/GPRC6A activation has also been implicated in cancer progression. GPRC6Ais activated by cations, amino acids and testosterone. The multi-liga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 83 publications
1
15
0
Order By: Relevance
“…Despite this, utilizing a rodent GPRC6A whole-body knockout model, oral administration of both l -arginine and l -ornithine significantly increased plasma GLP-1 TOTAL to a comparable magnitude in GPRC6A knockout and wild-type mice ( 138 ). However, as extensively discussed by Pi et al ( 133 , 139 ), caution should be taken when analyzing the reported effects. GPRC6A mouse knockout models are challenging due to variations in metabolic phenotype ( 140 , 141 ), which are reportedly influenced by environmental challenges and genetic differences in mouse strains ( 139 ).…”
Section: Current Status Of Knowledgementioning
confidence: 98%
See 1 more Smart Citation
“…Despite this, utilizing a rodent GPRC6A whole-body knockout model, oral administration of both l -arginine and l -ornithine significantly increased plasma GLP-1 TOTAL to a comparable magnitude in GPRC6A knockout and wild-type mice ( 138 ). However, as extensively discussed by Pi et al ( 133 , 139 ), caution should be taken when analyzing the reported effects. GPRC6A mouse knockout models are challenging due to variations in metabolic phenotype ( 140 , 141 ), which are reportedly influenced by environmental challenges and genetic differences in mouse strains ( 139 ).…”
Section: Current Status Of Knowledgementioning
confidence: 98%
“…However, as extensively discussed by Pi et al ( 133 , 139 ), caution should be taken when analyzing the reported effects. GPRC6A mouse knockout models are challenging due to variations in metabolic phenotype ( 140 , 141 ), which are reportedly influenced by environmental challenges and genetic differences in mouse strains ( 139 ). In addition, the translational validity of such studies is questioned because GPRC6A (in humans) presents an evolutionarily divergent genotype characterized by a gain-of-function polymorphism (GPRC6A KGKY ), which might alter the role of this receptor ( 133 ).…”
Section: Current Status Of Knowledgementioning
confidence: 98%
“…Yet, probably the most critical consequence of the identification of Gprc6a as a receptor of osteocalcin has been to allow the study of the biology of osteocalcin in humans as will be described below. More broadly, it gave to osteocalcin a more complete hormonal identity, which has now been confirmed by numerous independent cell culture studies, in vivo studies in multiple species and multiple disease models, by correlative studies in humans and as we will describe, human genetic evidence [37,42,45–120]. It was also confirmed even more recently by the generation of a new genetic model of Osteocalcin deficiency [50].…”
Section: The Foreseen Functions Of Osteocalcinmentioning
confidence: 78%
“…As for GC, they affect numerous physiological processes through their ability to modulate gene expression in a wide array of cell types (11,12). In the skeleton, GC are powerful inhibitors of Osteocalcin expression in osteoblasts, a regulation that was puzzling until evidence that osteocalcin is a hormone accumulated (13,14). Indeed, given the endocrine identity of osteocalcin, the inhibition of its expression by GC suggests that through a classical feedback loop osteocalcin may be a previously unappreciated physiological regulator of GC biosynthesis.…”
Section: Introductionmentioning
confidence: 99%